Evaluation of Daily Life Activities (Functional Outcomes) in Ischemic Stroke Patients With and Without Diabetes (Medical Forum Monthly, 2024)
Objective: To evaluate and compare the functional outcomes and daily life activities in ischemic stroke patients with and without diabetes.Study Design: Cross sectional study.Place and Duration of Study: This study was conducted in the Department of Neurology, Shaikh Zayed Postgraduate Medical Complex, Lahore from May 2013 to May 2014.Materials and Methods: This study was comprised 100 patients, and used Barthel Index Scoring System for measuring daily life activities in our stroke patients on admission, one month and 3 months after stroke event.Results: The lower Barthel index on admission and slower recovery during first 4 weeks in diabetic patients than non-diabetics while no significant differences were noted after 3 months of stroke onset between both groups.Conclusion: Functional outcomes of activities of daily life in diabetic stroke patients are slower than non-diabetics in first month after onset of stroke.